Czech Local Press Content: When More is Actually Less - Lenka Waschková Císařová, (Communication Today, 2025)
The development of Czech media during the last 25 years has been influenced by commercialisation, which has characterised its transformation from that of a communist regime to its current globalised context. The commercialisation of local media has manifested itself through the notable erosion of its particular local characteristics (delocalization). The main aim of the article is to find the answer to the question of how has the content of the particular local press changed in terms of localization or delocalization due to the commercialisation development trends. This text uses a case study approach (content analysis and in-depth interviews) to analyse the Vltava-Labe-Press (VLP) publishing house that largely dominates the Czech local press market. In the first phase I conducted a series of semi-structured in-depth interviews with editors-in-chief in the VLP’s newsrooms and managers in the VLP publishing house. This was followed by a quantitative content analysis of two newspapers between 1989 and 2009 focused on changes in editorial content and changes in the formal presentation of content. The main question of the case study is, how did the local press content published by Vltava-Labe-Press change between 1989 and 2009 in terms of localization and delocalization. The premise was that commercialisation leads to delocalization, diminishing local character and production of the content, and hence between 1989 and 2009 the share of converged and centrally produced contents increased in selected Czech local dailies. The analysis demonstrates an inverse relationship between management localization efforts and the manifestation of local content in the press. Consequently, the delocalized character of the Czech local press is likely to have an adverse effect on the democratic and political empowerment of local communities.